(untitled) (Research in Agriculture Livestock and Fisheries, 2018)
Avian influenza (AI) caused by Type A influenza virus is a global zoonosis, infecting vast majority of mammalian and avian species. Broilers are meat type birds and randomly reared and sold by the farmers in Bangladesh with poor biosecurity. This study was aimed to identify the Type and subtypes of AI viruses in the broilers of two live bird markets, Mymensingh. A total of 10 birds from each of the market were randomly selected, investigated by clinical, pathological, reverse transcriptase polymerase chain reactions (RT-PCR), sequencing and sequence analysis. Out of 20 birds investigated, 06 were sick, 02 were dead and 12 were apparently healthy. Clinically, the sick/dead birds did not reveal any changes typical to AI. During necropsy, the sick/dead birds showed congested lungs and moderate hemorrhages in the trachea. Such lesions was absent in the lungs of apparently healthy birds. Following histopathological examination interstitial pneumonia with bronchitis was seen in sick/dead birds. The RT-PCR protocol was adapted to identify matrix protein gene of Type A influenza virus and amplified 430bp fragment is even cases. To identify the sub types of AI viruses involved, hemagglutinin (HA) and neuraminidase (NA) gene specific RT-PCR was carried out. 1475bp and 1089bp amplicons specific to HA and NA genes of AI viruses were generated in 07 cases. The cDNAs of HA and NA genes were sequenced, edited and revealed that the AI virus circulated in the live bird market of Mymensingh city is H9N2 subtype. Two sick, one dead and four apparently healthy birds found to carry H9N2 AI virus. The H9N2 virus is naturally low pathogenic for poultry, has got public health significance, and may donate partial or even whole cassette of internal genes to generate novel human-lethal reassortants of AI viruses; this was main concern for AI viral outbreak investigation in this study. It needs to examine large number of samples from wider sources to trace the rate of mutation and subsequent reemergence of pandemic AI viruses. Res. Agric., Livest. Fish.5(2): 225-233, August 2018